Episthemological and methodological aspects of sozology - Krysiak, Marian P. (Studia Ecologiae et Bioethicae, 2005)
It seems necessary that the police surroundings should get known about the natural environmental protection which sozology is. During the research that I carried out among the policemen I’ve done the questionnare about information and ecological consciousness of the police. I’ve examined 500 policemen. Just 2 % of the surveyed brought the environmental protection to their mind, 98% wrongly thought just about ecology. This situation forces wider defining teh sozology and presenting its episthemological and methodological aspects. What is more it demands wider participation in police teaching programmes.